HPLC-MS analysis, antioxidant and hepatoprotective potential of okra fruit (Abelmoschus esculentus) against carbon tetrachloride induced hepatic damage - Hamza BELKHODJA; Fatima Z. LABBACI; Abderrahmane REMIL; Djilali BOUHADI; Mohammed HARIR; Fehmi BOUFAHJA (Notulae Scientia Biologicae, 2025)
This study exploits the bioactive components of the species Abelmoschus esculentus and examines the polyphenolic extract's antioxidant and hepatoprotective potential. The phytochemical characterization was performed using High-Performance Liquid Chromatography-Mass Spectrometry analysis, followed by the evaluation of the antioxidant activity in vitro and the study of the hepatoprotective potential against hepatic lesions induced by carbon tetrachloride in mice. Two main compounds were identified by HPLC-MS analysis: quercetin and kaempferol. The in vitro antioxidant activity of A. esculentus extracts showed interesting free-radical properties manifested by low IC50 values compared to ascorbic acid. The macerated aqueous extract of A. esculentus has an interesting hepatoprotective effect against the lesions induced by carbon tetrachloride in mice, as evidenced by weight gain, a normal hepato-somatic index, and improvement in biochemical parameters. A. esculentus is of considerable therapeutic interest as an alternative compound for preventing hepatic disorders and lesions.